The dynamical U(n) quantum group - Erik Koelink; Yvette Van Norden (International Journal of Mathematics and Mathematical Sciences)
We study the dynamical analogue of the matrix algebra M(n), constructed from a dynamical R-matrix given by Etingof and Varchenko. A left and a right corepresentation of this algebra, which can be seen as analogues of the exterior algebra representation, are defined and this defines dynamical quantum minor determinants as the matrix elements of these corepresentations. These elements are studied in more detail, especially the action of the comultiplication and Laplace expansions. Using the Laplace expansions we can prove that the dynamical quantum determinant is almost central, and adjoining an inverse the antipode can be defined. This results in the dynamical GL(n) quantum group associated to the dynamical R-matrix. We study a ∗-structure leading to the dynamical U(n) quantum group, and we obtain results for the canonical pairing arising from the R-matrix.